Nilai-nilai luhur Tari Kedempling dalam pembelajaran IPS berbasis teori belajar behavioristik - Fahmi Nur Ramadhan; Sariyatun Sariyatun (Jurnal Teori dan Praksis Pembelajaran IPS, 2020)
Social studies learning aims to prepare and transform students into good citizens. The theme of social studies is phenomena that occur in society in the past, present, and trends in the future. Therefore, local wisdom can be a study in social studies learning because it relates to society, both the rules that are obeyed and the cultural results created by the community. One of the local wisdoms that contains noble values in life is the Kedempling dance. Kedempling dance teaches that every human being must have a goal in life and to achieve that goal one must focus and work hard. Therefore, the Kedempling dance can be a material that can be conveyed to students, one of which is to achieve the social studies learning objectives through a Behavioristic approach. Behavioristic theory itself examines changes in human behavior. DOI: http://dx.doi.org/10.17977/um022v5i22020p114